Application of geologic-mathematical 3D modeling for complex structure deposits by the example of Lower-Cretaceous period depositions in Western Ust - Balykh oil field (Khanty-Mansiysk Autonomous District) - Perevertaylo (Perevertailo), Tatyana Gennadievna; Nedolivko, Nataliya Mikhailovna; Prisyazhnyuk, O.; Dolgaya, Tatiana Fedorovna (IOP Publishing, 2015)
The complex structure of the Lower-Cretaceous formation by the example of the reservoir BC[10]{1} in Western Ust - Balykh Oil Field (Khanty-Mansiysk Autonomous District) has been studied. Reservoir range relationships have been identified. 3D geologic-mathematical modeling technique considering the heterogeneity and variability of a natural reservoir structure has been suggested. To improve the deposit geological structure integrity methods of mathematical statistics were applied, which, in its turn, made it possible to obtain equal probability models with similar input data and to consider the formation conditions of reservoir rocks and cap rocks.
Keywords: 3D-моделирование; сложные структуры; месторождения; меловые отложения; нефтяные месторождения; Ханты-Мансийский автономный округ; природные резервуары; математическая статистика; Мезозой::Меловая